Sex Matters: Hippocampal Volume Predicts Individual Differences in Associative Memory in Cognitively Normal Older Women but Not Men - Zheng, Zhiwei; Li, Rui; Xiao, Fengqiu; He, Rongqiao; Zhang, Shouzi; Li, Juan (Frontiers in Human Neuroscience, 2017)
The hippocampus plays a prominent role in associative memory by supporting relational binding and recollection processes. Structural atrophy in the hippocampus is likely to induce associative memory deficits in older adults. Previous studies have primarily focused on average age-related differences in hippocampal structure and memory performance. To date, however, it remains unclear whether individual differences in hippocampal morphometry underlie differential associative memory performance, and whether there are sex differences in the structural correlates of associative memory in healthy older adults. Here, we used voxel-based morphometry (VBM) to examine the extent to which gray matter volume (GMV) of the hippocampus predicts associative memory performance in cognitively normal older adults. Seventy-one participants completed a cued recall paired-associative learning test (PALT), which consists of novel associations and semantically related associations, and underwent magnetic resonance imaging (MRI). We observed worse associative memory performance and larger variability for novel associations than for semantically related associations. The VBM results revealed that higher scores on associative memory for novel associations were related to greater hippocampal GMV across all older adults. When considering men and women separately, the correlation between hippocampal GMV and associative memory performance for novel associations reached significance only in older women. These findings suggest that hippocampal structural volumes may predict individual differences in novel associative memory in older women but not men.